Pembuatan Dekorasi Ruangan, Bros, Bunga Papan dari Sampah Plastik sebagai Upaya Mengurangi Pencemaran Lingkungan - Puswati, Desti; Devita, Yeni; Nita, Yureya; Alfianur, Alfianur; Yanti, Novi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
In addition to polluting the environment, various types of waste plastic waste are also tricky for nature to decompose because plastic waste is made from very carbon forgings, so it requires a lot of energy to spoil it. Solutions to reduce plastic waste by recycling, one of which is the creative sector. Creative industries can be launched through environmental initiatives, both collectively and individually, to turn plastic waste into something more useful. It can be utilized to improve the community's economy through collective ingenuity. By processing into handicrafts. It is community service method by delivering material on the benefits of waste recycling and the practice of making room decorations. The results of community service are in the form of skills in making room decorations and marketing through online handicrafts.